SUMBER-SUMBER HUKUM INTERNASIONAL DALAM PEMBENTUKAN DAN PERKEMBANGAN TATA HUKUM GLOBAL - Musliaroza, Muhammad Rizki; Asidiqi, Iqbal; Alfaizaly, Rezky Zico; Akbar, Syahrotul; Idris, Farid Muhammad; Ruhiyat, Adi; Guspita, Devika Rosa (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2026)
International law does not originate from a single source, but rather from a diverse and complementary set of sources. This study examines the sources of international law as set forth in Article 38 of the Statute of the International Court of Justice (ICJ), namely international treaties, international custom, general principles of law, judicial precedents, and legal doctrine. The objective of this study is to analyze the functional hierarchy, binding force, and the contribution of each source in shaping and developing the global legal order. The study employs a normative legal methodology using legislative, conceptual, and historical approaches, drawing on secondary data consisting of international treaties, ICJ judgments, academic literature, and international legal documents. The results of the analysis show that international treaties dominate dispute resolution practices at the ICJ, accounting for 48% of cases, while international custom continues to play an important role, particularly for non-party states. There has been a significant shift from custom-based sources toward formal codification through post-1945 multilateral treaties, in line with the increasing number of international treaties registered with the United Nations—from 312 (1945–1954) to 2,891 (2015–2023). This study confirms that the five sources of international law operate synergistically, rather than in an absolute hierarchy, and that their roles continue to evolve in tandem with the dynamics of contemporary international relations, including the emergence of non-state actors and cross-border legal issues such as climate change and cybersecurity